Rare-earth element analyses for iron-manganese crusts of the Pacific Ocean - Aplin, Andrew C; Michard, Annie; Albarède, Francis (PANGAEA, 2022)
Iron-manganese crusts were chosen from existing collections in order to cover as wide an area and depth range as possible. Sampling was concentrated in the Central Pacific seamount provinces where crusts are most commonly found coating lithic substrates. Rare earth element analyses were made on unleached material by inductively-coupled plasma atomic emission spectroscopy.
Keywords: Geochemistry; manganese micronodule; manganese nodule; ocean; sediment